The history of diplomatic protocol with the emphasis on French influence on diplomatic protocol and new cultural influences on today´s diplomatic protocol - Lukovicsová, Nicola (2015)
The Master's Thesis on "The History of Diplomatic Protocol with the Emphasis on French Influence on Diplomatic Protocol and New Cultural Influences on Today's Diplomatic Protocol" aims at introducing the topic of History of Diplomatic protocol and is further elaborating on the topic in terms of various influences on Diplomacy and Diplomatic protocol. The purpose was to show that the evolution of the practices, protocols and etiquette is a gradual process of change. Nowadays we live in the world strongly influenced by the European tradition that mainly comes from France. However, the changing world and process of globalization makes it easier for people to interact, share their values and spread their ideas.